The impact of Natura 2000 designation on agricultural land rents in Germany. (September 2019) - Koemle, Dieter; Lakner, Sebastian; Yu, Xiaohua
Abstract: Designation of Natura 2000 areas is a major cornerstone in the EU's biodiversity policy. However, it has triggered resistance from land users due to increased regulations on land use and related value change. This study first develops a theoretical model for rent change due to land regulation, and then empirically investigates whether farmland rents in Germany are affected by Natura 2000 designation. We use a matching procedure based on a zero-inflated beta generalized propensity score on German district level agricultural census data. Our results suggest that rental prices of grassland, arable land, and on average are affected negatively by Natura 2000.